2007
DOI: 10.1021/ma0713613
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Copolymerization of Vinylidene Fluoride with Hexafluoropropylene in Supercritical Carbon Dioxide:  Low Hexafluoropropylene Content Semicrystalline Copolymers

Abstract: The copolymerization of vinylidene fluoride with hexafluoropropylene (HFP) was carried out in supercritical carbon dioxide by precipitation polymerization using a continuous stirred tank reactor. Copolymers with ca. 10 mol % HFP were synthesized at 40 °C and pressures in the range of 207−400 bar using perfluorobutyryl peroxide as the free radical initiator. The effects of feed monomer concentration and reaction pressure were both explored at otherwise constant conditions. The rate of polymerization (R p) and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
83
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(86 citation statements)
references
References 47 publications
2
83
1
Order By: Relevance
“…In contrast, homopolymerizations of VDF and copolymerizations of VDF and HFP carried out in heterogeneous phase (precipitation) at lower pressures resulted in bimodal MWDs. [19,20,33] It can be concluded that adding HFP to the reaction mixture leads to successful solution copolymerizations at noticeably lower temperature and pressures than in the case of pure VDF (140 8C, 1 500 bar) for f HFP > 0.10.…”
Section: Resultsmentioning
confidence: 98%
“…In contrast, homopolymerizations of VDF and copolymerizations of VDF and HFP carried out in heterogeneous phase (precipitation) at lower pressures resulted in bimodal MWDs. [19,20,33] It can be concluded that adding HFP to the reaction mixture leads to successful solution copolymerizations at noticeably lower temperature and pressures than in the case of pure VDF (140 8C, 1 500 bar) for f HFP > 0.10.…”
Section: Resultsmentioning
confidence: 98%
“…Finally, for reactions at constant initiator concentration (such as the copolymerization reactions in CSTR at different pressures reported by Ahmed et al14), the following equation can be worked out combining Equation 32 and 35: …”
Section: Parameter Evaluationmentioning
confidence: 99%
“…In recent years, the heterogeneous free‐radical homopolymerization of vinylidene fluoride (VDF) and its copolymerization with hexafluoropropylene (HFP) have been the subject of several experimental studies. Precipitation,14–17 as well as dispersion polymerizations18–22 have been analyzed. The reason of such an interest is twofold.…”
Section: Introductionmentioning
confidence: 99%
“…20 The first continuous copolymerization of vinylidene fluoride (VDF) with hexafluoropropylene (HFP) in scCO 2 was recently reported to give semicrystalline copolymers. 22 This also has industrial significance, as VDF-HFP copolymers are an important class of materials with applications in tubing, valves, and membranes. 22 The excellent mass-transfer properties of scCO 2 mean that good molecular weight control is achievable in radical polymerization reactions.…”
Section: Polymer Synthesismentioning
confidence: 99%
“…22 This also has industrial significance, as VDF-HFP copolymers are an important class of materials with applications in tubing, valves, and membranes. 22 The excellent mass-transfer properties of scCO 2 mean that good molecular weight control is achievable in radical polymerization reactions. Gregory et al recently exemplified the controlled dispersion polymerization of methyl methacrylate through reversible addition fragmentation chain transfer (RAFT) in scCO 2 .…”
Section: Polymer Synthesismentioning
confidence: 99%